The new literacies of online reading comprehension: expanding the literacy and learning curriculum - Leu, Donald J.; McVerry, J. Gregory; O'Byrne, W. Ian; Kiili, Carita; Zawilinski, Lisa; Everett-Cacopardo, Heidi; Kennedy, Clint; Forzani, Elena (Journal of Adolescent & Adult Literacy, 2011)
73 citations (Crossref) [2023-10-31] tex.orcid-numbers: Kiili, Carita/0000-0001-9189-4094 tex.unique-id: ISI:000295394000002
Keywords: dept.cur

Surpassing normal: preparing teachers for diverse learners - Bower, Laura A; Sature, Amanda L (Action in teacher education, 2011)
Teacher education must prepare teacher candidates for diverse contexts and diverse learners. Such preparation involves teacher candidates unearthing their assumptions about diverse populations and understanding the roles candidates' own backgrounds play in these assumptions. Queer theory can facilitate this process through attention to culturally constructed notions of “normal” and “deviant.” This chapter investigates a strategy intended to identify teachers' cultural expectations through disrupting candidates' perceptions of “normal” students. Data sources include responses to a specific learning activity, interviews, and demographic surveys. Findings indicate that teacher candidates are reluctant to discuss certain demographic descriptors, such as race/ethnicity and sexual orientation, preferring to focus on students' interests and social behaviors. candidates' conceptions of a “normal” student mirror their own experiences. Interview responses suggest that the learning activity disrupted these conceptions. Implications point to the importance of discussing diversity in teacher education courses and the necessity of fieldwork in diverse contexts. © 2011, Copyright Association of Teacher Educators.
2 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/115-625-205-447-042 tex.type: [object Object]
Keywords: dept.cur